2013
DOI: 10.1093/bja/aet038
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of GABAA receptor activity by volatile anaesthetics is reduced by α5GABAA receptor-preferring inverse agonists

Abstract: L-655,708 and MRK-016 reduced the potentiation by inhaled anaesthetics of GABAA receptor activated by a low concentration of GABA. Future studies are required to determine whether this effect contributes to the memory preserving properties of inverse agonists after anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Previous studies have demonstrated that sevoflurane exposure can alter various neurotransmissions by enhancing GABAA receptor activity (Lecker et al . ), antagonizing NMDA receptor (Brosnan and Thiesen ), increasing glycine receptor function (Kira et al . ), and inhibiting nicotinic acetylcholine receptor or 5‐HT3 receptor function (Rada et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that sevoflurane exposure can alter various neurotransmissions by enhancing GABAA receptor activity (Lecker et al . ), antagonizing NMDA receptor (Brosnan and Thiesen ), increasing glycine receptor function (Kira et al . ), and inhibiting nicotinic acetylcholine receptor or 5‐HT3 receptor function (Rada et al .…”
mentioning
confidence: 99%
“…Sevoflurane is one of the most commonly used volatile anesthetic agents. Previous studies have demonstrated that sevoflurane exposure can alter various neurotransmissions by enhancing GABAA receptor activity (Lecker et al 2013), antagonizing NMDA receptor (Brosnan and Thiesen 2012), increasing glycine receptor function (Kira et al 1998), and inhibiting nicotinic acetylcholine receptor or 5-HT3 receptor function (Rada et al 2003;Stevens et al 2005). While no study has examined the effects of sevoflurane on cannabinoid receptor function, studies have shown that isoflurane, a similar volatile anesthetic, can interact with CB1 receptor (Starker et al 2006).…”
mentioning
confidence: 99%
“…Such a compound could be useful as a therapeutic agent for disorders of cognition (Atack, 2010), post-stroke recovery (Clarkson et al, 2010) or anesthetic-induced amnesia (Lecker et al, 2013;Zurek et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this idea, animal behavioral studies demonstrated that pre-treatment with the α 5 GABA A R negative modulator, L-655 708, was indeed able to reverse short-and long-term memory impairment in mice anesthetized with isoflurane [87,89]. Furthermore, L-655 708 and another α 5 GABA A R-selective negative allosteric modulator, MRK-016 (Table 1, 2), significantly inhibited isoflurane and sevoflurane-potentiated GABA currents in hippocampal neurons of wild-type mice, whereas the GABA response in α 5 GABA A R-knockout mice was not affected by the anesthetics [90]. On a related matter, pre-treatment with α 5 IA in human subjects managed to selectively counter the deterioration in the ability to recall a word list following alcohol consumption [46,91].…”
Section: Prevention Of Amnesiamentioning
confidence: 94%